Association between Heterologous Prime-boost Vaccination and Coronavirus Disease 2019 Among People in Phayao Province: A Matched Case-Control Study - phisitphattanaphong, Dara; Thammakun, Theerawut; Kaladee, Akaphol (Nursing Journal CMU, 2023)
Coronavirus disease 2019 is a respiratory disease that can cause severe illness if patients do not get COVID-19 vaccination. This research aimed to explore the association between heterologous prime-boost COVID-19 vaccination and COVID-19 incidence among people in Phayao province. This matched case-control study was conducted with a sample of 385 adults aged 18 years and over in Phayao province who were selected using the stratified two-stage random sampling method with a case/control ratio of 1:4 (77 cases and 308 controls). Data were collected in September 2022 and then analyzed for frequency, percentage, mean, standard deviation, and conditional logistic regression. The results showed that getting a heterologous prime-boost COVID-19 vaccination was significantly associated with incidence of COVID-19. Those who had received such a vaccination regimen were 56.0% less likely to be infected with Coronavirus 2019 than those who were not vaccinated, with statistical significance (ORadj = 0.44, 95% CI = 0.23-0.87, p = 0.017). The results of this study provide important information for promoting COVID-19 vaccination. People can use this information to decide on heterologous prime-boost vaccination for prevention of COVID-19.